Development of E-Picture Story Book media based on the Steinberg method with local wisdom to improve vocabulary skills of low-grade students - Yunita, Dyah Ayu Ihza; Purwati, Panca Dewi; Sismulyasih SB, Nugraheti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Beginning reading is an important foundation for mastering reading skills. If students do not achieve the indicators of initial reading skills, they will not be able to master further reading skills. This research is motivated by the learning outcomes of students who have not reached the Minimum Completeness Criteria (KKM) in vocabulary introduction material. The purpose of this study is to evaluate the feasibility and effectiveness of E-Picture Story Book media based on the Steinberg Method and contain local wisdom in improving student learning outcomes related to initial reading skills in grade II of elementary school. The research method used is research and development (R&D) with the Borg and Gall development model. The product validity test was carried out by validators who were material experts and media experts, while grade III elementary school students were used as subjects for product trials. The results of this study show that the media feasibility test obtained a result of 88% with a very feasible predicate, while the feasibility test from material experts obtained a score of 92% with a very feasible predicate. The results of the effectiveness test can be seen from the comparison between the pretest and posttest results which show an improvement, with an average N-Gain of 0.58 and a significance value (2-tailed) of 0.000, which is less than 0.05. The conclusion of the results of this researcher shows that overall, the E-Picture Story Book media Based on the Steinberg Method Loaded with Local Wisdom is declared feasible and effective in improving the vocabulary skills of grade III students of SDN Sangge. The conclusion of this study shows that there is an increase in learning outcomes in vocabulary recognition skills in grade II students.